12. The Effect Of Neem Leaves (Azadirachta Indica) Extract To The Blood Profile Of Male Rat (Rattus Norvegicus) Infected With Trypanosoma Evansi Of Krueng Raya Isolat - Atika Agusty; Yudha Fahrimal; Triva Murtina Lubis; Muhammad Hambal; Zuhrawaty NA; Arman Sayuti (Universitas Syiah Kuala, 2018)
This study aimed to determine the ability of neem leaf extract to maintain the normal blood profile of white male rat (Rattus norvegicus) infected with Trypanosoma evansi. A total of 24 male white rats were divided into 6 groups. The K0 group as the negative control received no T. evansi infection and no neem leaf extract. Furthermore, K1 group (positive control) only infected with T. evansi, K2 and K3 were given neem leaf extract 50mg/kg BW and 100mg/kgBW, while K4 and K5 were given neem leaf extract 400mg/KgBW and K5 800mg/kgBW. The neem leaf extract was administered for 3 consecutive days after infection established. The blood of the rats was collected to determine the amount of erythrocyte and leukocyte, hemoglobin level and hematocrit value. The data were analyzed using Analysis of Variance (ANOVA) through SPSS for Windows 16.0. The averages (+SD) of erythrocyte of K0, K1, K2, K3, K4, and K5 were 5,64±0,57; 2,31±1; 1,93±0; 0; 2,55±0,33; and 2,56±0,48. The amount of leukocyte were 4,46±1,09; 4,45±1,91; 5,25±0; 0; 8,42±1,66; and 8,14± 5,17. The value of hemoglobin were 12,00±0,47; 10,50±0,57; 4,30±0; 0; 5,60±0,20; and 9,03±0,66. The level of hematocrit 38,00±1,83; 25,00±9,90; 15±0; 0; 18,00±2,65, and 20,75±1,71. The result showed that the administration of neem leaf extract with doses 400mg/kgBW and 800mg/kgBW were difference significantly (P0.05) compare to the positive control of rats, but could not equalize blood profile of uninfected white male rats